TINJAUAN YURIDIS PENGGUNAAN DINAR DAN DIRHAM DI INDONESIA (STUDI KASUS PUTUSAN 202/Pid.Sus/2021/PN.Dpk TENTANG PASAR MUAMALAH) - Nabila, Nabila; Arini, Diah (Journal of Islamic Law Studies, 2021)
For centuries, the dinar and dirham have been recognized as the most stable and sharia-compliant official trading instruments. In Indonesia, dinars and dirhams may be used with specific qualifications. However, the precedent for arresting scholar Zaim Saidi for organizing a muamalah market using dinar-dirham is a bad practice of punishing innovation in the use of dinar-dirham, which reduces the development of the sharia economy in Indonesia. The acquittal of the Depok District Court (PN) No. 202/Pid.Sus/2021/PNDpk proves the ignorance of the state (in this case, the police and the prosecutor's office) regarding the concept of using dinars and dirhams themselves. This study aims to educate the public and state civil servants regarding the use of dinar and dirham in Indonesia and support their use as currency in Indonesia. This research method is a normative juridical research method with a conceptual approach, a statute approach, and a case approach based on the Depok District Court decision. The study results indicate that the judge's consideration in deciding this case was correct, and it is hoped that the results of the appeal to this case can strengthen the decision of the District Court at the first level. The development of the use of the dinar-dirham must also be encouraged to strengthen the Indonesian economy. Hopefully, this case will not become a scourge for sharia economic activists to carry out economic innovations using dinars and dirhams in the future.